Prostate Cancer Specificity of PCA3 Gene Testing: Examples from Clinical Practice - Marks, Leonard S (MedReviews, LLC, 2008)
A specific marker for early prostate cancer would fill an important void. In initial evaluations of the prostate cancer antigen 3 (PCA3) gene vis-à-vis serum prostate-specific antigen (PSA) levels, the gene offers great promise. At the cellular level, PCA3 specificity for cancer is nearly perfect because of the gross overexpression of the gene by cancer cells. As a clinical test for early prostate cancer, heightened specificity is also seen in urine containing prostate cells from men with the disease. PCA3 gene testing holds valuable potential in PSA quandary situations: (1) men with elevated PSA levels but no cancer on initial biopsy; (2) men found to have cancer despite normal levels of PSA; (3) men with PSA elevations associated with varying degrees of prostatitis; and (4) men undergoing active surveillance for presumed microfocal disease.